2019
DOI: 10.18510/hssr.2019.7156
|View full text |Cite
|
Sign up to set email alerts
|

Audience Culture in the Reception of Text: Black Campaigns on Online Media During Indonesia's 2014 and 2019 Presidential Elections

Abstract: Purpose of the study: This study seeks to explore the influence of culture on audiences' responses to online negative campaigns during Indonesia's 2014 and 2019 presidential elections. It shows that voter behavior is not determined entirely by media messages, as voters' decisions are strongly informed by their cultural and family backgrounds. Methodology: Negative campaign messages conveyed through online mass-media coverage were used as the main object of this study. These messages were analyzed categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The news about camel urine, clothes bleach, blood thinners, nicotine, Pancasila herbal concoctions have indicated that the media in this study intend not only to convey information or to entertain, but they also bring their and sensitive and promotional (propaganda) purposes. In line with Abdullah [52], the media consciously plan propaganda to build significant power in influencing audiences. Besides, during the COVID-19 pandemic, the media are involved in institutional domination (supremacy), which is effective in spreading COVID-19 information.…”
Section: Discussionmentioning
confidence: 99%
“…The news about camel urine, clothes bleach, blood thinners, nicotine, Pancasila herbal concoctions have indicated that the media in this study intend not only to convey information or to entertain, but they also bring their and sensitive and promotional (propaganda) purposes. In line with Abdullah [52], the media consciously plan propaganda to build significant power in influencing audiences. Besides, during the COVID-19 pandemic, the media are involved in institutional domination (supremacy), which is effective in spreading COVID-19 information.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Campbell and Connelly (2015, p. 273), this new media enables users to become involved in everyday religious activities, and as such informs social traditions, behaviors, and attitudes. User respond to new media based on their backgrounds and their ideologies, not being passive consumers but rather active readers with their own particular interests (Abdullah et al, 2019).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…However, the media actually has an interest in producing specific meanings that further its agenda. It does not merely convey information or entertainment; rather, it is consciously used for propaganda and ideological purposes, reaffirming the status quo and thereby supporting the ruling class (Abdullah et al, 2019).…”
Section: Discourse and Media Representationmentioning
confidence: 99%